Habilidades auditivas e de linguagem de crianças com deficiência auditiva acompanhadas no serviço de atenção à saúde auditiva do hospital das Clínicas da UFMG - Leticia Macedo Penna (2013)
Introduction: Hearing loss can cause great impact oc a child's listening skills, oral and written language development. An efficient clinical intervention process is critical to the child's hearing loss process of rehabilitation. Moreover, socioeconomic factors, social behavior and family environment can also influence the child's development and should be investigated. Objectives: To assess the oral and written language development and listening skills of children, hearing aids user, ages six to 10 years old, adapted for the period 2008 ti 2010 at Auditive Health Attention Service of HC/UFMG; and the association with intervention process, socioeconomics, clinical and psychosocial factors. Methods: An analytic transversal study was made in an Auditive Health Attention Service. 110 children with hearing loss, between 6 and 10 years old, using hearing aids, with light to deep hearing loss level were evaluated. For evaluation of oral language was used the expressive vocabulary and phonological subtest of the Language Test for Young Children ABFW, the skills of reading, writing and arithmetic were evaluated using the Learning Performance Test (TDE), and for evaluation of the hearing used Speech Perception Test (GASP) and Phoneme Discrimination Picture Test (TDFD). The children's parents responded to a structure questionnaire to collect data from medical history and also socioeconomic questionnaires (RAF) and "Strenghs and Difficulties Questionnaire" (SDQ). A descriptive analysis of the frequency distribution of categorical variables and analysis of the measures of central tendency and dispersion for continuos variables were used. For the univariate analysis, Kruskal-Wallis ANOVA, chi-square and Fisher Exact was used. For multivariate analysis a logistic regression, with the initial model composed of variables with ap value <0.20 in the univariate analysis was used. The level of significance was set at 5%. Results: Regarding the diagnosis of auditory study popukation, the most common type observes was a loss of 94.4% for both ears. For the degree of the hearing loss, there is a great number of children in the moderately severe / severe (43.6%) group. For the configuration of audiometric curve, both ears, the descending curve was the most frequent (56.3% in the right ear and 53.6% in the left ear). An association between the degree of hearing loss and age at diagnosis, age of adaptation of hearing aids, the type of communication used by children and performance on auditory tests erre observed. Most of the children, disregard of the hearing loss level, had abnormal development of listening skills, oral and written language in all evaluated groups. For the oral language, 74.5% of children had abnormal vocabulary and 92.7% had alterations in phonology area. The overall evaluation of school performance tests showed a 93.6% of underperformed children. For the GASP hearing test, the best results were observed with respect to TFDF test for all the evaluated groups. The multivariated analysis initial model that tested the lexical develipment with several factors association is formed with age, hearing loss risk factors, hearing loss degree, phonoaudiological evaluations, phonotherapy frequency, kind of school, mother's age, mother's and father's scholarship, per capita income, TDE, TFDF and RAF results. The final multivariate model proved the association between the Vocabulary Test and the Phoneme Test (OR 0,81; IC 0,73-0,89). Conclusions: Disregarding with the hearing loss degree, most of the deaf children had abnormal development of listening skills and oral written language. This result may be related to the characteristics of clinical intervention process that these children made, considering that the hearing diagnosis, the hearing aids adaptation age and the rehabilitation process occurred late. No relationship was found between lexical development and environment factors, socioeconomic and social behavior. However, longitudinal studies should be conducted to better understand the relationship of these factors with the development of deaf children. This study reinforces the importance of auditory processing stimulation, especially phonemic discrimation ability, throughout the process of deaf chidren rehabilitation. The skills assessment of oral and written language and hearing of deaf children should be performed periodically, so that the rehabilitation process may be reevaluated and the treatment plan are prepared according with each individual evolution.